Analisis penerimaan bank digital dengan UTAUT 2 pasca pandemi - Taufan, Sonny; Wardani, Deni (Lembaga Pengembangan Manajemen dan Publikasi Imperium, 2023)
The purpose of this study is to examine the effect of performance expectations, business expectations, social influence, facility conditions, hedonic motivation, price values, habits, and perceived trust on intentions and actual use of digital banks. The measurement method in this study used a questionnaire distributed online to digital bank users in the Bekasi, Depok, Jakarta and Tangerang areas. Processing data using descriptive quantitative methods and sampling methods using purposive sampling. Data analysis used the PLS-SEM analysis method. The results of this study can be concluded that the influence of performance expectations, business expectations, social influence, facilitating conditions, price values, habits, and perceptions of trust has a significant influence on intention to use and hedonic motivation has no effect on intentions to use digital banks. Public interest statements The benefits of the results of this research can be a recommendation to the general public to see what factors can be considered in using digital banks, so that the general public can find out what factors can influence the use of digital banks.